PENGARUH INTENSITAS KOMUNIKASI PEER GROUP DAN TERPAAN PESAN PROMOSI JUDI ONLINE DI MEDIA SOSIAL TERHADAP PERILAKU ADIKTIF BERMAIN JUDI ONLINE - Nanda Deristia Maharani; Nurist Surayya Ulfa; Sunarto Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Online gambling has become a digital trend that has increased during the pandemic. Online gambling is of great interest to people from all walks of life, both adults, young people and even minors. The most popular online gambling games in Indonesia are slots. Online gambling activities in Indonesia are classified as activities that are illegal and fall into the category of cyber crime. The mass media reports that the motivation for the tendency to commit criminal acts is caused by the desire to play online gambling. The aim of this study was to determine the effect of the intensity of peer group communication and exposure to online gambling promotional messages on social media on addictive behavior in playing online gambling together. The theory used in this research is Bandura's Social Learning Theory. This research is explanatory quantitative. In a typical sample, this study used a snowball sampling technique. This study used a sample of 85 respondents, aged 18-44 years, gambled at least >5 game sessions in the past week, and had seen online gambling promotions on social media. The data analysis technique used is multiple linear regression analysis. The results of the study stated in addition, together there is an influence of the intensity of peer group communication and exposure to online gambling promotional messages on social media on the addictive behavior of playing online gambling was 55,9%. and it was known that the magnitude of the effect of the effective variable intensity of peer group communication was more dominant by 29, 61 %